2005
DOI: 10.1002/path.1908
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA mutation and histological type in breast carcinoma: high frequency of mutations in lobular carcinoma

Abstract: Mutations in the PIK3CA gene have recently been reported in different human neoplasms, including breast cancer. This paper reports the results of a systematic analysis of PIK3CA mutations in different histological types of breast carcinoma. One hundred and eighty invasive breast carcinomas, comprising 74 ductal, 56 lobular, 22 mucinous, 20 medullary, and eight papillary, were selected on the basis of their histological type in a consecutive series of 780 breast cancers. Exons 1-20 of the PIK3CA gene were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
68
6
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 35 publications
13
68
6
1
Order By: Relevance
“…31,[36][37][38] For instance, in colorectal carcinomas, their frequency was significantly greater in highgrade and advanced carcinomas (32%) than in lowgrade tumors (3%). 31 Similarly, a higher rate of PIK3CA mutations was found in invasive lobular and ductal breast carcinomas than in other histologic types associated with more favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31,[36][37][38] For instance, in colorectal carcinomas, their frequency was significantly greater in highgrade and advanced carcinomas (32%) than in lowgrade tumors (3%). 31 Similarly, a higher rate of PIK3CA mutations was found in invasive lobular and ductal breast carcinomas than in other histologic types associated with more favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…25,27,28 However, in contrast to other epithelial cancers, such as colorectal 31,36 and breast carcinomas, 37,38 no correlation has been found between the distribution of PIK3CA mutations and grade and stage of disease. Given the recently reported role of PIK3CA mutations in tumor invasion and metastases, 29 we analyzed the PIK3CA status in a large series of endometrial adenocarcinomas and compared the results, between PIK3CA-mutated and PIK3CA-nonmutated groups, with the clinicopathological parameters known to be related to prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has recently been suggested that PIK3CA inhibitor could be used in the treatment of basal-like BC [18]. Contrasting this, some authors have found an association with invasive lobular carcinoma; a type frequently occurring in the luminal-like class of BC [19], and with the resistance to hormonal therapy [20]. Thus, these predominantly small or preclinical studies have yielded a diversity of observations and conclusions.…”
Section: Introductionmentioning
confidence: 87%
“…D'autres gènes sont altérés par délétion, mutation ou perte d'expression, comme CDH1 (cadhérine E) dans les cancers lobulaires, TP53, et BRCA1 et BRCA2 dans les cancers héréditaires. La sous-unité catalytique P110 de la phosphatidyl-inositol-3 kinase est fréquemment mutée [23]. De nombreuses amplifications et délétions récurrentes ciblant des régions chromosomiques précises ont été identifiées par hybridation génomique comparative.…”
Section: Quels Sont Les Gènes Altérés Dans Les Cancers Du Sein ?unclassified